O processo de ensino e aprendizagem no ensino de ciências: uma análise das práticas de avaliação - Morales, Cinthia Junger de Souza (2013)
Evaluation in schools is a necessary procedure in order to redirect the teaching and learning process in all areas of knowledge.This dissertation submits the partial result of a research work carried out in the M.A. in Education in Sciences in the Amazon. The goal of this work is to analyze the teaching and learning process starting from evaluation practices in the teaching of sciences at Junior High School Grade 6 in a public school in the city of Manaus. We have opted for a qualitative research. The research subjects were pupils and teachers of the Junior High School Grade 6. Participating observation, individual semi-structured interviews with teachers and groups of pupils, and document studies: monthly planning, evaluation instruments, school bulletin, and the Pedagogic Political Project were used for data collection. We have noticed that the teaching and learning process in Natural Sciences still happens in a fragmented, isolated and decontextualized manner, mostly based on textbooks only through reading, copying and questionnaires on the text within the classroom space, data processing room and the library. Therefore, a traditional and classificatory evaluation practice, however, different from the concept of the Pedagogic Political Project of a school that defends knowledge construction through the diagnostic, formative and summative evaluation. The need arises for a Natural Science teaching that is organized towards a knowledge construction and an evaluative practice that is dialogic and meditational, in order to make sense for the life of the pupils and would allow for the transformation of the society where we live for the Education in Sciences so that such learning becomes useful and employed in the daily life of the student. After all, the impact science and technology cause in society requires that the school teach and learn for life, interacting science, technology, society and the environment through values and atitudes. It is,therefore, important that the school as whole with its professionals cast its view towards the window of the world, always challenging the quest for overcoming the reproduction for the production of knowledge to achieve a learning in partnership also with the non-formal spaces, full of natural riches. To propose the drafting of evaluative reports for the understanding and interpretation of the phenomenon of the construction of knowledge by teachers and students. And to suggest to professionals programs of a continued education relative to the teaching, learning and evaluation for the Education in Sciences, since teaching, learning and evaluation are interconnected. After all, Science has been through advances, discoveries, disasters, transformations bringing about changes to our complex society, that is, plural and diverse, and the school needs to accompany such evolution